UV‐Selective Optically Transparent Zn(O, S)‐Based Solar Cells. Issue 11 (20th September 2020) - Lopez-Garcia, Alex J.; Bauer, Andreas; Fonoll Rubio, Robert; Payno, David; Jehl Li-Kao, Zacharie; Kazim, Samrana; Hariskos, Dimitrios; Izquierdo-Roca, Victor; Saucedo, Edgardo; Pérez-Rodríguez, Alejandro
Abstract : This work reports experimental evidence of a photovoltaic effect in transparent UV‐selective Zn(O, S)‐based heterojunctions. Zn(O, S) has a strong interest for the development of UV‐selective solar cells with high transparency in the visible region, required for the development of nonintrusive building‐integrated photovoltaic (BIPV) elements as transparent solar windows and glass‐based solar façades. By anion alloying, Zn(O, S) mixed crystal absorbers can be fabricated with different sulfur content across the whole compositional range. This allows adjustment of the bandgap of the absorbers in the 2.7–2.9 eV region, maximizing absorption in the UV, while keeping a high level of transparency. Zn(O, S) alloys with composition corresponding to S/(S + O) content ratios of 0.6 are successfully grown by sputtering deposition, and first glass/FTO/NiO/Zn(O, S)/ITO device prototypes are produced. The resulting devices present an average visible transmittance (AVT) of 75% and present photovoltaic effect. By introducing a thin C60 film as electron transport layer (ETL), charge extraction is enhanced, and devices show an efficiency of 0.5% and an AVT > 69%. The transparency of these devices can potentially allow for their ubiquitous installation in glazing systems as part of nonintrusive BIPV elements or to power Internet of Things (IoT) devices and sensors as an integrated transparent component. Abstract : Fabrication of transparent Zn(O, S)‐based wavelength‐selective solar cells is reported. It is the first report showing a transparent device based on this mixed crystal as absorber. By introducing C60 as electron transport layer (ETL), a device with structure FTO/NiO/Zn(O, S)/C60 /BCP/ITO is fabricated, presenting power conversion efficiency (PCE) = 0.48% with an average visible transmittance (AVT) = 69.3% and light utilization efficiency (LUE) = 0.34%.